Study on the production of ¹⁷⁷Lu for medical purposes at the Dalat Research Reactor. Part 1. Study on production of ¹⁷⁷Lu at the Dalat Research Reactor - Nguyen , Ngoc Tuan; Duong , Van Dong; Bui , Van Cuong; Pham , Thanh Minh; Nguyen , Thi Hang (Nuclear Science and Technology, 2015)
Lutetium-177 (177Lu) radioisotope used for medical purposes has been produced at the Dalat Nuclear Research Reactor during 2012-2014. The product was synthezed by the activation reaction 176Lu (n,γ) 177Lu. The target was Lutetium oxide with an abundance of 176Lu being 2.59% and the irradiation was conducted with a neutron flux of 2.1013 n cm-2 s-1. The activity of the 177Lu product was 39,59 Ci g-1 after 108 hous of the irradiation. The yield of this method was much higher compared to those of the reaction 176Yb(n, γ)177Yb → 177Lu + β- which for the same time could be 15mCi/50mg only. Because of low specific radioactivity the preparation of 177Lu made from the activation of 176Yb cannot be applied for the medical purposes. Additionally, the separation yield of 177Lu from 177Yb is rather low, it is usualy of approximately 70%.